Empirical Findings on the Relationship of Energy Consumption, Gross Domestic Product Per Capita and Carbon Dioxide (CO2) Emissions - Agasalim, Alasgarova Aygun (International Journal of Energy Economics and Policy, 2024)
The energy industry drives all economic sectors and improves people’s well-being. Energy supply reliability underpins national security, economic growth, and global stability. Energy use, especially electricity, affects GDP per capita. Power-to-weight ratio is energy consumption per person. The main purpose of the study, as used in the literature, is to investigate the relationship between carbon dioxide (CO2) emission and energy consumption, per capita gross domestic product for Azerbaijan using the Toda-Yamamoto causality test using annual data for the period 1991-2021. According to the results of the research, while there is no relationship between energy consumption and GDP, an increase in per capita income reduces CO2 emissions; it was also found that there is a unidirectional causality running from CO2 emissions to an increase in per capita income. An increase in energy consumption per capita leads to a decrease in CO2. However, there is bidirectional causality running both from energy consumption per capita to CO2 and from CO2 to per capita income. As a result, a 1% increase in energy consumption per capita causes a 0.946% increase in CO2. It has been determined that a 1% increase in gross domestic product per capita does not cause a 0.086% decrease in CO2.